PENGARUH PUPUK ORGANIK CAIR HASIL FERMENTASI KOTORAN SAPI TERHADAP PERTUMBUHAN DAN PRODUKSI SAWI (Brassica juncea L.) - Asrijal Asrijal; Nur Sabrina MT; Murmayani Murmayani; Ambo Upe (Universitas Andi Djemma Palopo, 2022)
Fermented cow dung has high fiber and moisture content, and improves soil porosity and fertility. The experiment was carried out in Ujung Village, Lilirilau District, Soppeng Regency, fromÂ JanuaryÂ to May 2022. The aim of the experiment was to determine the growth and production of mustard greens due to the administration of POC fermented cow dung. This study was arranged using a Randomized Block Design (RBD) with 4 groups. The variables consisted of cow manure liquid organic fertilizer P0 (0 ml/L water), P1 (25 ml/L water), P2(50 ml/L water), P3 (75 ml/L water), P4 liquid (100 ml/ L of water), the application time consists of 2 levels: 10 HST, 20 HST, 30 HST. Parameters observed were plant height, number of leaves, fresh weight per sample. Based on the results of the study, it was shown that the effect of a dose of 100 ml/L of water tended to show the best growth and production of the observed parameter components